La sensibilidad emocional y su influencia en el rendimiento deportivo de un adolescente de 15 años de la Federación Deportiva de Los Ríos - Mora Salazar, Julisa Tatiana (2022)
In this study, the psychological diagnosis of emotional sensitivity of a 15-year-old adolescent from the Los Ríos Province of the Babahoyo canton, who plays his sports life in the Los Ríos Sports Federation, in the wrestling discipline, will be analyzed. will provide psychological care to help you manage those negative emotions that lead you to become frustrated and discouraged. The work is feasible since there is a prudent time to carry out the interviews, the predisposition of the patient in each of the sessions, as well as in the treatment and competent information.